2004
DOI: 10.1210/jc.2004-0388
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Endocannabinoid System in Early Human Pregnancy

Abstract: In recent years, it has been demonstrated that high circulating levels of the endogenous cannabinoid anandamide, resulting from low expression of its metabolizing enzyme fatty acid amide hydrolase (FAAH), may contribute to spontaneous miscarriage and poor outcome in women undergoing in vitro fertilization. The site of action of this compound, however, has not been determined. In this study, we examined the distribution of the cannabinoid receptors, CB1 and CB2, and the endocannabinoid-metabolizing enzyme FAAH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 27 publications
3
39
0
1
Order By: Relevance
“…It has been shown that the expression of placental CB1 receptor protein is elevated 2.5-fold in spontaneous miscarriage in the first trimester compared with levels observed in voluntary termination ). In addition, Trabucco et al found that the immunostaining of the CB1 receptor is poorly detected in placental villi from elective surgical terminations, which supports earlier observations from our laboratory that the expression of CB1 receptor mRNA and protein is not readily detected in the first-trimester placentae (weeks 9-13 of gestation; Helliwell et al 2004). However, for gestational age-matched placentae of weeks 7-8, the expression of CB1 receptor protein in the trophoblast, mesenchymal core and decidua was approximately twofold lower in spontaneous miscarriage than in elective surgical termination (Taylor et al 2011).…”
Section: Endocannabinoids and Laboursupporting
confidence: 85%
“…It has been shown that the expression of placental CB1 receptor protein is elevated 2.5-fold in spontaneous miscarriage in the first trimester compared with levels observed in voluntary termination ). In addition, Trabucco et al found that the immunostaining of the CB1 receptor is poorly detected in placental villi from elective surgical terminations, which supports earlier observations from our laboratory that the expression of CB1 receptor mRNA and protein is not readily detected in the first-trimester placentae (weeks 9-13 of gestation; Helliwell et al 2004). However, for gestational age-matched placentae of weeks 7-8, the expression of CB1 receptor protein in the trophoblast, mesenchymal core and decidua was approximately twofold lower in spontaneous miscarriage than in elective surgical termination (Taylor et al 2011).…”
Section: Endocannabinoids and Laboursupporting
confidence: 85%
“…PCR primers were as follows: CB1 forward, 5Ј-atgaagtcgatcctagatggccttgcaga-3Ј, and CB1 reverse, 5Ј-tcacagagcctcggcagacgtg-3Ј (27). CB1 primers amplify the 1.5-kb coding region of the CB1 receptor.…”
Section: Methodsmentioning
confidence: 99%
“…The antibody was affinity purified and recognized recombinant FAAH expressed in HEK293 cells, but exhibited no detectable immunoreactivity to wild-type cells and recognized a single band by Western immunoblot (data not shown). Additionally, Helliwell et al (2004) have demonstrated the utility of this antibody for immunocytochemistry (Harkany et al, 2003;Helliwell et al, 2004). All three antibodies were generated in the laboratory of authors CK and KM at the University of Washington.…”
Section: Immunohistochemistrymentioning
confidence: 99%